Trend in the consumption of carbapenems in a public-private partnership hospital - Otoya Durand, Enrique (2021)
Background: Hospitals should evaluate their antibiotics use and the relationship with local bacterial resistance. Objective: Identify the trend in the consumption of carbapenems and explore its correlation with multiresistant Pseudomona aeruginosa cultures. The study: An ecological study was carried out in a hospital in Lima – Peru. We measured the consumption of imipenem and meropenem in one year and calculated the correlation with multiresistant Pseudomona aeruginosa cultures. Findings: The consumption of imipenem had no significant variations, but meropenem had a tendency to decrease. There was a significant positive correlation between the defined daily dose of meropenem according to hospital stay and discharges with multiresistant Pseudomona aeruginosa cultures (0.71, p=<0.01 and 0.64, p=0.02, respectively). Conclusion: There was a downward trend in the consumption of meropenem and this had a significant correlation with the decrease in multiresistant Pseudomona aeruginosa cultures.